Social discourse in the songs used at Ede prayer mountain, Osun State, Nigeria (2018)
Studies have discussed the significance of traditional and contemporary songs and prayers in various religious domains across cultures. What we sing and/or pray about is to a very large extent socially constructed since prayer and music have communicative roles, especially in a religious context. Existing studies have focused attention on the spiritual constructs of songs and prayers but adequate attention has not been paid to the social implications of the songs used in Christian worship, particularly in non- conventional church spaces such as prayer mountains. This study investigates various social discourses in the songs used at Ede Prayer Mountain, Osun State. Nigeria, using the social constructionism as theoretical framework. Through ethnomusicological method of data collection, interviews were conducted with eight purposively selected participants at Ede Prayer Mountain. Also, songs recorded during the study were content analysed with the purpose of highlighting various social narratives in the songs. The study, concludes that the songs used at Ede Prayer Mountain are not purely religious in their discourse but to a large extent are entwined with social commentary